Artificial Intelligence in Medicine in Europe AIME’03 - Garbay, Catherine; Baud, Robert; Keravnou-Papailiou, Elpida (My University, 2005)
This double issue of AIM hosts a selection of expanded versions of papers that were presented at the Sixth Conference on Artificial Intelligence in Medicine Europe (AIME’97), held in Grenoble, 23–26 March 1997, under the auspices of the European Society for Artificial Intelligence in Medicine. The AIME Society was established in 1986 following a highly successful workshop held in Pavia the year before. The Society’s aims are to foster fundamental and applied research in the application of AI techniques to medical care and medical research, and to provide a forum for reporting significant results achieved at biennial conferences
Keywords: Computer science; Artificial intelligence; Medicine--Europe; Medicine--Research